Peningkatan Tata Sosial dan Pembangunan Infrastruktur Jembatan bagi Masyarakat Desa Minanga Timur Kab. Minahasa Tenggara - Steve W.M Supit; Marike Kondoj; Herry Langi; Heidy Pesik; Jeanely Rangkang (JURNAL UMBANUA, 2022)
The community service program was conducted in Minanga Timur Village, Southeast Minahasa Regency. This village was chosen due to its potential as a part of tourism area that could contributes the improvement of tourism industry y at Southeast Minahasa Regency. This program aims to increase the knowledge and skills of small business enterprises in digital marketing, to facilitate the government officers on village financial management and to construct a simple bridge for student access. Based on the program evaluation, the small enterprises were able to design and produce packaging that can contribute to competitive advantage for marketing products. On the other hand, the village officers are expected to implement proper financial and administration management. The bridge construction has also provided a safety and convenient access for the students to and from school. The social empowerment at Minanga Timur Village could supports a creation of the independent village that will benefits the communities wellfare